PELAKSANAAN KEBIJAKAN ALOKASI DANA DESA DALAM MEMPERDAYAKAN MASYARAKAT DESA: STUDI KASUS DESA CATURTUNGGAL, KECAMATAN DEPOK, KABUPATEN SLEMAN - Hasnop Putra Minang; Kumba Digdowiseiso; Eko Sugiyanto (Universitas Nasional, 2021)
Allocation of village funds is a balance between central and regional financial funds received by districts / cities, which in the distribution for each village is distributed proportionally, namely at least 10% (ten percent). The allocation of village funds is intended for the implementation of village government and community empowerment. This research uses qualitative methods with a descriptive approach. The results showed that normatively and administratively the management of village fund allocations was carried out well, but in substance it had not yet touched the true meaning of empowerment. In addition, some stakeholders have not carried out their roles optimally, only the village head as the implementing team dominates the management of the village fund allocation. The paternalistic culture of the village community causes the community to be indifferent and put full trust in the village head in the management of village fund allocations, as well as the dominance of the sub-district in the preparation of a letter of accountability which causes a lack of village independence. Therefore, this study aims to describe the effectiveness of village government policies (namely the village fund allocation policy) in supporting the empowerment of village communities. The results of this study indicate that the allocation of village funds serves as a stimulus to encourage the Caturtunggal Village community to develop and maximize their potential. The physical development budget is also directed and focused on improving the economy of the village community by involving them in projects and other social activities in the village and by involving them to care about their village development.